2016
DOI: 10.1108/ijse-11-2014-0243
|View full text |Cite
|
Sign up to set email alerts
|

Credit constraints and their impact on farm household welfare

Abstract: This study aims at identifying factors affecting formal credit constraint status of rural farm households in Vietnam's North Central Coast region (NCC). Using the Direct Elicitation method (DEM), we consider both internal and external credit rationing. Empirical evidences confirm the importance of household head's age, gender and education to household's likelihood of being credit constrained. In addition, households who have advantages in farm land size, labour resources and non-farm income are less likely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 55 publications
6
29
0
Order By: Relevance
“…Model (2) in Table 4 contains the results on the probability of obtaining informal credit. The results show that kinship and friendship affect the probability of getting informal loans but in the opposite direction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Model (2) in Table 4 contains the results on the probability of obtaining informal credit. The results show that kinship and friendship affect the probability of getting informal loans but in the opposite direction.…”
Section: Resultsmentioning
confidence: 99%
“…Finance is at the core of economic activities and rural finance is an important force for agricultural development, rural economic growth, and farmer income growth. However, imperfections in rural financial markets and limitations of formal financial institutions lead to credit constraints in most developing countries [1,2]. Rural people often have limited or no access to formal credit because their incomes are unstable, they have limited or no collateral, and high transaction costs because information asymmetries [3].…”
Section: Introductionmentioning
confidence: 99%
“…They indicate that non-constrained households have higher monthly expenditure than constrained counterparts. Similarly, Tran et al [29] found a lower consumption expenditure among credit constrained households compared to randomly selected households. Similar findings are also found in Briggeman et al's [40] research on US farm and nonfarm households, and in Li and Zhu's [33] study on Chinese rural households.…”
Section: Credit Constraint and Households' Welfarementioning
confidence: 88%
“…Credit constraint was measured via the direct elicitation technique described by Boucher and colleagues [43] and often utilised for studying the phenomenon (see [17,29,32]). This method uses survey questions to separate the households with credit constraint from those without credit constraints.…”
Section: Sampling Methods and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation